Pengalaman ibu dalam merawat anak dengan thalassemia mayor di rumah singgah thalassemia Banda Aceh - Novita, Nia Hairu; Usman, Said; Rani, Hafnidar A (Holistik Jurnal Kesehatan, 2025)
Background: Thalassemia major is a chronic disease that, when diagnosed in children, can have significant emotional, cognitive, and daily impacts, especially on parents, and can also cause stress. Purpose: To explore mothers' experiences caring for children with thalassemia major at a thalassemia shelter in Banda Aceh. Method: This study used a qualitative design with a grounded theory approach. Interviews were conducted between August and September 2021 with six mothers caring for children with thalassemia major. Five main focus areas were explored: mothers' knowledge of thalassemia, concerns about their children's future, financial difficulties, family/social support received, and family resilience. Results: Parents believed that thalassemia major was not a hereditary disease, but they expressed concerns about their children's future, including the possibility of marriage. Finances were a major concern for families with children with thalassemia major, given that their children require routine monthly medication. Support from the surrounding community, both physical and material, was perceived to have a significant positive impact on mothers and families with children with thalassemia major. Families generally accept their child's condition. Conclusion: Caring for a child with thalassemia major requires time, effort, and expense. Mothers with more experience caring for children are generally more accepting of their child's condition. Suggestion: Healthcare workers in hospitals must be able to fulfill their roles broadly, not only as nurses but also as advocates for children and families concerned about thalassemia.   Keywords: Caregiving; Child; Maternal Experience; Thalassemia Major.   Pendahuluan: Thalassemia mayor merupakan penyakit kronik yang apabila terjadi pada anak dapat memberi dampak, khususnya terhadap orang tua dalam hal emosional, kognitif, dan kesehariannya dan juga dapat menimbulkan stress pada anak. Tujuan: Untuk mengeksplor pengalaman ibu dalam merawat anak dengan thalassemia mayor di rumah singgah thalassemia Banda Aceh Metode: Penelitian ini menggunakan rancangan kualitatif dengan pendekatan grounded theory pada 6 orang ibu yang merawat anak dengan thalasemia mayor dan dilaksanakan pada Agustus–September 2021. Adapun yang digali dalam penelitian ini menyangkut 5 hal yaitu pengetahuan ibu tentang thalasemia, kekhawatiran terhadap masa depan anak, kesulitan finansial, dukungan keluarga /sosial yang diterima, dan ketahanan keluarga. Hasil: Orang tua menganggap bahwa thalassemia mayor bukanlah penyakit keturunan, terdapat kecemasan terhadap masa depan anak, salah satunya adalah kemungkinan untuk bisa berumah tangga. Keuangan menjadi permasalahan utama bagi keluarga dengan anak thalassemia mayor mengingat bahwa anaknya membutuhkan pengobatan setiap bulan secara rutin, dukungan lingkungan sekitar baik secara real maupun materil dirasa sangat berdampak positif kepada ibu dan keluarga yang memiliki anak dengan thalassemia mayor, keluarga umumnya menerima kondisi penyakit anak mereka. Simpulan: Dibutuhkan waktu, tenaga, dan biaya dalam merawat anak dengan thalassemia mayor, biasanya ibu yang telah memiliki pengalaman lebih lama dalam merawat anaknya dapat lebih menerima kondisi penyakit anaknya. Saran: Tenaga kesehatan di tatanan rumah sakit agar dapat menjalankan perannya secara luas selain caring, namun juga mencakup peran sebagai advokasi bagi anak dan keluarga tentang penyakit thalassemia.   Kata Kunci: Anak; Merawat; Pengalaman Ibu; Thalassemia Mayor.